Effect of Pigment Concentration on Visual and Performance Quality of TPU Resin in Injection Molding - Isma Wulansari; Bella Bestari; Ariya Wedian; Debby Wulandary (Universitas Islam Raden Rahmat, Malang, 2025)
The visual quality of Thermoplastic Polyurethane (TPU)-based products is significantly influenced by the dispersion of pigments and the moisture content in the material, particularly during the injection process. This study aims to evaluate the effect of ultramarine and fluorescent pigment concentrations on the visual quality and performance of TPU products, as well as to analyze the water content derived from raw materials, such as calcium carbonate (CaCO₃), in the masterbatch formulation. The methods employed include measuring water content using the HydroTracer FLV HT3 tool and conducting visual analysis of injection results, which vary in pigment concentration and drying temperature. The results show that high water content, especially from calcium carbonate type B (up to 0.0733%), contributes to visual defects in the form of white spots and colour inhomogeneity. The fluorescent red pigment exhibits the best visual performance at a concentration of 0.07%, whereas the purple pigment shows poor colour stability. Drying at 110°C for 2 hours is proven to be optimal for producing a clean and uniform TPU surface. This study emphasises the importance of raw material moisture control and pigment formulation optimisation in maintaining consistent TPU product quality, especially in applications with high aesthetic demands.